The influence of brand experience on brand authenticity and brand love: an empirical study from Asian consumers' perspective. Issue 5 (7th October 2020) - Safeer, Asif Ali; He, Yuanqiong; Abrar, Muhammad
Abstract : Purpose: This research investigates the effects of multidimensional brand experiences (i.e. behavioral, intellectual, affective and sensory) on brand authenticity and brand love from the Asian consumers' perspective. Design/methodology/approach: This research collected primary data from 418 consumers on global brands, and it tested the proposed hypotheses by using partial least squares structural equation modeling (PLS-SEM). Findings: The findings indicate that sensory and affective experiences have direct significant impacts on brand love, while intellectual and behavioral experiences have nonsignificant impacts on brand love. Overall, intellectual, behavioral, affective and sensory experiences positively influence brand authenticity, which in turn have substantial positive impacts on brand love. Research limitations/implications: This study investigated consumer behavior in a broader sense, and consumers from 13 Asian countries participated in this research. Future research may collect data on a larger scale from Asian countries to generalize the results. Practical implications: By following brand authenticity as an essential positioning tool and implementing several experiential marketing strategies, global managers can develop brand-loving consumers in Asia. Originality/value: Under the parasol of attribution theory, this research explores the relationships among the multidimensional brand experiences, brand authenticity and brand love from the Asian perspective.